The mediating effect of empathy in the relationship between humanistic practice competence and caring ability among newly employed nurses - Rongxiu Jin; Yi Wang; Ying Shan; Jiuqun Li (International Journal of Africa Nursing Sciences)
Background: The transition period for newly employed nurses is critical for the development of professional competencies, particularly in humanistic practice and caring ability. While previous research has established the importance of humanistic practice competence in nursing, the mediating role of empathy in the enhancement of caring ability remains underexplored. This study aims to analyze the relationship between humanistic practice competence and the caring abilities of newly hired nurses, specifically focusing on the mediating role of empathy in this context. Methods: A cross-sectional study was conducted Among 129 newly employed nurses from a tertiary hospital in Shenzhen. Three validated instruments—the Humanistic Practice Competence Assessment Scale, the Interpersonal Reactivity Index Questionnaire (Empathy Ability Scale), and the Caring Ability Inventory (CAI)—were employed to collect data. Descriptive statistics were used to analyze the scores of humanistic practice competence, empathy, and caring ability. Correlation analysis and mediation analysis were performed to examine the relationships between these variables. Results: The findings highlighted that newly employed nurses excelled in humanistic practice competence with an average score of 106.50 ± 18.79 but did not meet the international standard in caring ability, scoring only 187.00 ± 21.62.The analysis demonstrated that newly employed nurses exhibited a humanistic practice competence score exceeding the average benchmark (106.50 ± 18.79), while their caring ability (187.00 ± 21.62) fell below established international standards.A significant positive correlation was identified between humanistic practice competence and caring ability. Furthermore, empathy was found to mediate the relationship between humanistic practice competence and caring ability, with an indirect effect value of 0.495, which accounted for 86.84 % of the total effect. Conclusion: This study highlights the pivotal role of empathic capacity in enhancing humanistic practice competence and caring ability among newly employed nurses, providing empirical support for nursing administrators to develop targeted intervention programs. The findings suggest that educational strategies should prioritize strengthening novice nurses’ humanistic cognition and professional identity, while systematically implementing humanistic practice protocols. Through clinical immersion, these practitioners can progressively refine their humanistic literacy, with particular emphasis on optimizing nurse-patient communication through evidence-based interaction techniques. Such multidimensional cultivation enables continuous delivery of high-quality, efficient, and patient-centered care that meets contemporary healthcare expectations.